2005
DOI: 10.1126/science.1112835
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Approach to the Percolation of Sticky Nanotubes

Abstract: Percolation is a statistical concept that describes the formation of an infinite cluster of connected particles or pathways. Lowering the percolation threshold is a critical issue to achieve light and low-cost conductive composites made of an insulating matrix loaded with conductive particles. This has interest for applications where charge dissipation and electrical conductivity are sought in films, coatings, paints, or composite materials. One route to decreasing the loading required for percolation is to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
197
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(205 citation statements)
references
References 27 publications
(12 reference statements)
5
197
1
1
Order By: Relevance
“…By contrast, even very weak attractive interactions, caused, e.g., by the presence of the matrix material (21), significantly lower the PT, although we cannot rule out the existence of a regime outside the range of validity of our approach, where attraction might do the opposite (22). We confirm earlier speculation that there are two different regimes with a different local structure depending on the strength of the attractive interactions (11,23), but in addition we make plausible the existence of two additional regimes at higher interaction strengths where the percolating network is either built up from nanotube bundles or is kinetically frozen and no longer in equilibrium.…”
Section: Andriy V Kyrylyuk* and Paul Van Der Schootsupporting
confidence: 77%
See 2 more Smart Citations
“…By contrast, even very weak attractive interactions, caused, e.g., by the presence of the matrix material (21), significantly lower the PT, although we cannot rule out the existence of a regime outside the range of validity of our approach, where attraction might do the opposite (22). We confirm earlier speculation that there are two different regimes with a different local structure depending on the strength of the attractive interactions (11,23), but in addition we make plausible the existence of two additional regimes at higher interaction strengths where the percolating network is either built up from nanotube bundles or is kinetically frozen and no longer in equilibrium.…”
Section: Andriy V Kyrylyuk* and Paul Van Der Schootsupporting
confidence: 77%
“…As is well known, the PT of conductive filler particles decreases in inverse proportion to their aspect ratio, a rule of thumb that is generally valid for elongated and flat particles alike (9,10). Recent experiments on the percolation of singlewalled carbon nanotubes (SWNTs) in aqueous dispersions (11,12) have also shown that a remarkable lowering of the PT can be achieved by making use of weak attractive interactions between the SWNTs (11).…”
Section: Andriy V Kyrylyuk* and Paul Van Der Schootmentioning
confidence: 98%
See 1 more Smart Citation
“…61 Equilibrium statistical mechanics predicts an exponential decrease in φ c at moderate attraction. 63,64,67 For strong attraction (w p ≃ 20-40k B T ) and large aspect ratio (λ ≃ 500-1000) such theories predict unphysical values for φ c , many orders of magnitude too small. This is not surprising, since the SWCNTs of interest are not in thermal equilibrium but form a glassy network.…”
Section: B Scaling Electronic Type and Film Durabilitymentioning
confidence: 99%
“…The formation of extended networks of particles dispersed in a fluid gives rise to a discontinuous change in the rheological [1][2][3][4][5] and electrical [6][7][8][9] properties of the dispersion at concentrations around the so-called percolation threshold. Historically, percolation theory was first used by Flory [10] to explain the phenomenon of gelation in thermosetting polymers.…”
Section: Introductionmentioning
confidence: 99%